Mechanotransduction of cells under physical constraints - Low, Agnes Fang Ting. (2009)
In this report, a direct quantitative way to measure the mechanotransduction of cells under physical constraints was discussed. This was accomplished by both microcontact printing and cell traction force microscopy study. A flexible polyacrylamide (PAL) gel embedded with fluorescent microbeads was polymerized on an activated glass surface. Adhesive islands were created on the surface of the gel or directly on activated glass surfaces by microcontact printing. Rat aorta cells were cultured on these islands. The cells spread to take on the shape and size of the islands. Cell traction force was then quantified by mapping displacement fields of the fluorescent microbeads within the micron-sized adhesive islands of defined shape and size. The results drew the relationship between cell traction force and various cell shapes.